The future of the United Nations system : potential for the twenty-first century - Alger, Chadwick F., 1924- (United Nations University Press, 1998)
"Twenty-two scholars from all continents contribute twelve chapters that encompass prevention of violence, creating economic and social structures that sustain human fulfilment, sharing and protecting the commons, and peace education. The search for future potential, based on experience in these twelve "laboratories," leads to sixty-six recommendations for new institutions and programmes on issues that include controlling weapons, humanitarian intervention, collaboration between UN peacekeepers and NGOs, human rights, economic policies, advancement of women, refugees, ecological security, communications, and peace education. These recommendations are brought together in a concluding chapter and summarized in an appendix."--Jacket.